Structural racism and the impact on incarcerated midlife women - Juana Hutchinson-Colas; Mary Cathryn Earnhardt; Afsara Mannan; James McGreevy; Gloria A Bachmann (BMC, 2022)
Abstract High recidivism rates indicate that current forms of imprisonment may be an ineffective response to problems that mainly burden those ensconced in poverty and marginalization. Homelessness, unemployment, racial disparities, drug use, and mental illness, disappear from public view when the afflicted individuals are relegated to a life behind bars. Women are the fastest growing prison population and most incarcerated women are from Black and Latinx groups. Structural racism encompasses the many ways in which society fosters racial discrimination through mutually reinforcing unfair systems of housing, education, employment, earnings, benefits, credit, media, health care, and criminal justice. In turn, this behavior reinforces discriminatory beliefs, values, and distribution of resources. Structural racism pervades every aspect of society, including the carceral system, from policing to prosecutorial decisions, pretrial release processes, sentencing, correctional discipline, and even reentry. Women constitute a minority within the carceral system, and as a result, their unique health care needs, especially during the midlife period, are inadequately addressed and often overlooked. There is also a general lack of gender sensitivity and special considerations in existing jail and prison policies and practices. This commentary highlights the impact of structural racism on the arrests and incarceration of women, and discusses their special health and wellness needs, with emphasis on midlife women. It also illuminates the need to address structural racism and its ripple effects within the carceral system.